2013
DOI: 10.1590/s1519-69842013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Ecological characterisation of the Colombian entomopathogenic nematode Heterorhabditis sp. SL0708

Abstract: The entomopathogenic nematode Heterorhabditis sp. SL0708 (Rhabditida: Heterorhabditidae) isolated from soil in Alcalá, Valle del Cauca (Colombia) was characterised ecologically using Galleria mellonella larvae (L) (Pyralidae: Galleriinae) as hosts. The effect of temperature on the viability, infectivity and reproduction, and of moisture on infectivity and storage in liquid were evaluated in infective juveniles (IJs). Significant differences were found in the viability, infectivity and reproduction of the IJs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…The hermaphroditic individual lays some of its eggs in the host's body cavity and retains the remainder of the eggs inside its uterus. This phenomenon is confirmed by observations of Boff et al (2001) and Wang and Bedding (1996) who analyse the growth cycle of H. bacteriophora. Wang and Bedding (1996) observed the life cycle of H. bacteriophora using an initial dose of 1 IJ.…”
Section: Discussionsupporting
confidence: 80%
“…The hermaphroditic individual lays some of its eggs in the host's body cavity and retains the remainder of the eggs inside its uterus. This phenomenon is confirmed by observations of Boff et al (2001) and Wang and Bedding (1996) who analyse the growth cycle of H. bacteriophora. Wang and Bedding (1996) observed the life cycle of H. bacteriophora using an initial dose of 1 IJ.…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that these isolates cannot persist in soil with low moisture level. The low potential of Heterorhabditis to survive low moisture level and desiccation has been discussed by Grewal et al (2006) , Mukuka et al (2010) , and Mejia-Torres and Saenz (2013) . However, the result of this study is contrary to the results reported for H. indica strain T2 (geographical origin: Thailand) which has been reported to infect G. mellonella larvae at moisture level as low as 3% ( Maketon et al, 2011 ), whereas Fijian isolates of H. indica were unable to cause any mortality at 5% moisture level.…”
Section: Discussionmentioning
confidence: 99%
“…In current study, even though the optimum concentration was 1000 IJ/ml for the storage experiment, poor storage stability was observed for native isolates of H. indica which is slightly higher when compared to Colombian Heterorhabditis sp. SL0708 (survive only up to 8 weeks) ( Mejia-Torres and Saenz, 2013 ). Low longevity in H. indica population has also been reported by Shapiro-Ilan et al (2006) .…”
Section: Discussionmentioning
confidence: 99%
“…Temperatures between 16-10 °C as observed in Porto Amazonas during winter usually reduces EPN efficacy (Klein, 1990;Mejia-Torres and Sáenz, 2013). However, winter temperatures seemed to be high enough to assure nematode capture during the entire year, even because samples were kept at 25 ºC in the laboratory, what favored the infection.…”
Section: Discussionmentioning
confidence: 99%